The Role of the National Police Super App in Improving the Quality of Public Services in Gorontalo City: A Community Perspective - Siti Nurcahyati Abdussamad; Sri Yulianty Mozin; Auralia Davina Salsabila (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
This study analyzes the effectiveness of the Polri Super App in improving the quality of public services in Gorontalo City, particularly in digital services such as SKCK, SIM, and STNK administration. Using a qualitative descriptive approach supported by interviews, observations, and documentation, the research applies Duncan's effectiveness indicators—goal achievement, integration, and adaptation—to assess the performance of the application. The findings show that the Polri Super App has facilitated faster, more practical, and easily accessible services, contributing to improved public service effectiveness. However, its implementation remains suboptimal due to persistent obstacles, including additional administrative requirements during SKCK collection, limited public knowledge stemming from inadequate socialization, and unequal digital adaptation among community groups. Younger and digitally literate users adapt more quickly, whereas older, rural, and low-literacy users experience difficulties accessing digital services. Overall, the Polri Super App partially fulfills its intended goals but requires enhanced socialization efforts, improved digital literacy support, and service procedure refinement to optimize its role in strengthening public service delivery in Gorontalo City.